Static hyper-polarizability of open shell molecules computed at the FSMRCCSD level using constrained variational approach - Bag, Arijit; Bhattacharya, S.; Pal, S. (International Conference on Recent Advances in Spectroscopy - Theoretical, Astrophysical and Experimental Perspectives, 2010)
In recent years, there has been a significant development in the analytic derivatives of energy with respect to electric fields based on the state-of-the-art multi-reference coupled-cluster method using Lagrangian based constrained variational approach. So far, the Lagrangian based Fock space multi-reference coupled cluster (FSMRCC) method has been successfully used to calculate electrical dipole moment and polarizability of open shell molecules, particularly, doublet radicals at the ground state and the electronic excited states of closed shell molecules. In this article, Lagrangian based FSMRCC method has been implemented for the first time for calculation of hyper polarizabilites of a few doublet radicals such as OH, OF, NO and NO(2). Orbital-relaxed finite field FSMRCC values are reported for comparison.